2013
DOI: 10.3892/mmr.2013.1270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP3A4*18B polymorphisms and interactions with OPRM1 A118G on postoperative fentanyl requirements in patients undergoing radical gastrectomy

Abstract: Abstract. The present study aimed to investigate the effect of cytochrome P450 3A4 (CYP3A4)*18B polymorphisms and the interaction of the µ opioid receptor gene (OPRM1) A118G and CYP3A4*18B polymorphisms on postoperative fentanyl analgesia in Chinese Han patients undergoing radical gastrectomy. In total, 97 patients scheduled to undergo radical gastrectomy under general anesthesia were enrolled in this study. Post-operative patient-controlled intravenous analgesia of fentanyl was administered as analgesia up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
1
7
1
1
Order By: Relevance
“…Another study in female-only sample of acute postoperative pain following hysterectomy or myomectomy revealed the association of 118G allele with higher fentanyl consumption for adequate pain relief but not with postoperative nausea and vomiting induced by fentanyl intravenous analgesia [187]. Finally, a recent study in patients undergoing radical gastrectomy showed the interaction between OPRM1 A118G SNP and cytochrome P450 3A4 ( CYP 3 A 4)*18B polymorphisms that jointly affect postoperative fentanyl analgesia so that patients with OPRM1 AA and CYP 3 A 4*1*18B genotypes received fewer fentanyl doses compared with other genotype groups [188]. These findings are in line with previously reported results on a combined effect of OPRM1 and COMT common functional polymorphisms on morphine postoperative analgesia and central side-effects.…”
Section: Nature and Painmentioning
confidence: 99%
“…Another study in female-only sample of acute postoperative pain following hysterectomy or myomectomy revealed the association of 118G allele with higher fentanyl consumption for adequate pain relief but not with postoperative nausea and vomiting induced by fentanyl intravenous analgesia [187]. Finally, a recent study in patients undergoing radical gastrectomy showed the interaction between OPRM1 A118G SNP and cytochrome P450 3A4 ( CYP 3 A 4)*18B polymorphisms that jointly affect postoperative fentanyl analgesia so that patients with OPRM1 AA and CYP 3 A 4*1*18B genotypes received fewer fentanyl doses compared with other genotype groups [188]. These findings are in line with previously reported results on a combined effect of OPRM1 and COMT common functional polymorphisms on morphine postoperative analgesia and central side-effects.…”
Section: Nature and Painmentioning
confidence: 99%
“…While the influence of A118G genotype on intravenous (IV) fentanyl has been evaluated in several studies mostly in Asian patients in the context of post-operative analgesia [12][13][14][15][16][17][18], only one study examined its effect for early labor analgesia [19]. However, fentanyl is often offered in North America to women in early labor in an effort to delay or avoid receiving neuraxial analgesia.…”
Section: Oprm1 and Intravenous Fentanyl For Labor Analgesiamentioning
confidence: 99%
“…Of importance, these findings of a pharmacogenetic effect of A118G on spinal fentanyl or epidural sufentanil, with lower dose requirements in laboring women with the G118 allele, are in disagreement with most if not all other studies examining the influence of A118G genotype and opioid analgesia [6], whether one evaluates post-operative IV fentanyl consumption [12][13][14][15][16][17][18], spinal morphine for post-cesarean pain [21,24,25], IV morphine for postoperative pain [26][27][28][29][30][31] or oral morphine for chronic cancer pain [5,32,33].…”
Section: Oprm1 and Epidural Sufentanil For Labor Analgesiamentioning
confidence: 99%
“…The frequencies of CYP3A4 ∗ 1G and CYP3A5 ∗ 3 alleles were 22.7–38.99% ( Hu et al, 2007 ; Zhang et al, 2010 , 2011 ; Yuan et al, 2011 ; Zhu et al, 2012 ; Xin et al, 2014 ) and 73.3% ( Zhu et al, 2012 ; Xin et al, 2014 ), respectively, and CYP3A4 ∗ 1G allele is highly genetically linked with the CYP3A5 ∗ 3 allele. Several studies indicate that CYP3A4 ∗ 1G is associated with altered CYP3A4 activity ( Fukushima-Uesaka et al, 2004 ) and may be responsible for the interindividual differences in the pharmacokinetics or pharmacodynamics of tarcolimus ( Shi et al, 2011 ; Zhu et al, 2012 ; Li et al, 2013 , 2014 ), atorvastatin ( Gao et al, 2008 ; He et al, 2014 ), cyclosporine ( Hu et al, 2007 ; Qiu et al, 2008 ), and postoperative fentanyl requirements ( Zhang et al, 2010 , 2011 ; Liao et al, 2013 ); CYP3A5 ∗ 3 allele is associated with a non-functional protein due to a premature termination codon. Therefore, altered activity of CYP3A4 and CYP3A5 resulting from genetic polymorphisms may affect the formation of active metabolite and the antiplatelet effect of the drug subsequently.…”
Section: Introductionmentioning
confidence: 99%